Learning Philosophy in Indonesian Islamic Universities: A Narrative Study of Theology and Islamic Philosophy Students - Ulya Ulya (AL-ISHLAH: Jurnal Pendidikan, 2026)
In Indonesia, philosophy is often stigmatized as impractical, confusing, or threatening to faith, despite limited evidence reflecting students’ lived experiences. This study explores how Theology and Islamic Philosophy students experience learning philosophy within Islamic higher education. A narrative inquiry design was employed with eight purposively selected final-year students (n = 8) from four State Islamic Universities in Central Java. Participants were drawn from Theology and Islamic Philosophy departments. Data were collected narrative frames and semi-structured interviews, and analyzed using thematic narrative analysis. Trustworthiness was ensured through member checking, peer debriefing, audit trails, and reflexive journaling. Participants initially perceived philosophy as intellectually demanding and potentially threatening to faith, leading to academic and spiritual anxiety. Through active, reflective, and dialogical engagement, they gradually negotiated these tensions and reinterpreted philosophy as a meaningful resource for understanding faith and life. This transformation fostered enhanced critical reasoning, inclusivity, and reflective problem-solving practices.The findings suggest that students’ negative preconceptions can be reshaped through pedagogical approaches that emphasize reflection and dialogue. Incorporating guided discussions and narrative writing into philosophy instruction may support deeper engagement and reduce perceived conflicts with faith. Such strategies contribute to more constructive and meaningful learning experiences in Islamic higher education.